The effectiveness of methanol extract and fractinations fromleaves of mangroveSonneratia albaand Bruguiera gymnorrhizafor the prevention of white spot syndrome virus (WSSV) infection in black tiger shrimp Penaeus monodon - Muliani, Muliani,; Susianingsih, Endang (Indonesian Society of Scientific Aquaculture (ISSA), 2018)
ABSTRACT The experiment aimed to determine the effectiveness of mangrove leaves (Sonneratia alba and Bruguiera gymnorrhiza) extracts for prevention of WSSV infection in black tiger shrimp, Penaeus monodon. Mangrove leaves (S.alba and B. gymnorrhiza) were taken from Maros and Pangkep Regency, respectively. Mangrove leaves dried approximately for two weeks, made into flour, extracted using 80% methanol, and then evaporated. The yield partitioned using two types of solvents, theywere butanol and dietyleter. Anti WSSV activity test was done by injection method with the ratio of mangrove extract and WSSV was 2:1 as much as 100 µL/ind. The treatment were; A). Water fraction of S. alba + WSSV suspention; B). Butanol fraction of S. alba + WSSV suspention; C). Dietyleter fraction of S. alba+ WSSV suspention; D). Methanol extract of S. alba + WSSV suspention; E). Water fraction of B. gymnorrhiza + WSSV suspention; F). Butanol fraction of B. gymnorrhiza + WSSV suspention; G). Dietyleter fraction of B. gymnorrhiza + WSSV suspention; H). Methanol extract of B. gymnorrhiza + WSSV suspention; I). Positive control (WSSV suspention without mangrove extract). Each treatment was repeated three times with 10 days of rearing period. The results showed that the highest activity of anti-WSSV from S. alba was in dietyleter fraction and the methanol extract, while the highest activity of anti-WSSV from B. gymnorrhiza was in butanol fraction. The dietyleter fraction and the methanol extract of S. alba and the butanol fraction of B. gymnorrhiza were capable to stimulate immune response of shrimp and were effective in deactivating WSSV furthermore it increased the black tiger shrimp survival rateto 100%. Keywords: antiviral, white spot syndrome virus (WSSV), mangrove herbs, S. alba, B. gymnorrhiza, Penaeus monodon ABSTRAK Penelitian ini bertujuan untuk mengetahui efektivitas ekstrak dari daun mangroveSonneratia. alba dan Bruguiera gymnorrhizauntuk pencegahan infeksi WSSV pada udang windu, Penaeus monodon. Daun mangroveS.alba dan B. gymnorrhiza masing-masing diambil dari Kabupaten Maros dan Kabupaten Pangkep. Daun mangrove dikering anginkan selama dua minggu, dibuat tepung, diekstraksi dengan metanol 80%, dan dievaporasi. Rendemen yang diperoleh dipartisi menggunakan dua jenis pelarut yaitu butanol dan dietileter. Uji aktivitas anti WSSV dilakukan metode penyuntikan dengan perbandingan ekstrak mangrove dengan WSSV 2:1sebanyak 100 µL/ekor. Perlakuan yang diujikan adalah; A). Fraksi air S. alba + suspensi WSSV; B). Fraksi butanol S. alba + suspensi WSSV; C). Fraksi dietileter S. alba+ suspensi WSSV; D). Ekstrak metanol S. alba+ suspensi WSSV; E). Fraksi air B. gymnorrhiza + suspensi WSSV; F). Fraksi butanol B. gymnorrhiza + suspensi WSSV; G). Fraksi dietileter B. gymnorrhiza + suspensi WSSV; H). Ekstrak metanol B. gymnorrhiza + suspensi WSSV; I). Kontrol positif (suspensi WSSV tanpa ekstrak mangrove). Masing-masing perlakuan diulang tiga kali dengan lama pemeliharaan 10 hari. Hasil penelitian menunjukkan bahwa aktivitas anti WSSV S. alba tertinggi pada fraksi dietileter dan ekstrak metanol, sedangkan aktivitas anti WSSV B. gymnorrhiza tertinggi pada fraksi butanol. Fraksi dietileter dan ekstrak metanol S. albaserta fraksi butanol B. gymnorrhiza mampu menstimulasi respons immun udang dan efektif dalam menonaktifkan WSSV sehingga meningkatkan sintasan udang windu hingga 100%. Kata Kunci: anti viral, white spot syndrome virus (WSSV), herbal mangrove, S alba, B. gymnorrhiza, udang windu